Imaged Based Authentication System dengan Reduced Difference Expansion - Muhammad Ali Sya'roni; Yanuar Nurdiansyah; Diksy Media Firmansyah (INFORMAL: Informatics Journal, 2022)
Authentication is an important step in a system. Text-based authentication is an authentication alternative that is currently widely used. However, text-based authentication has the disadvantage of being ineffective when users have multiple accounts. This weakness can be overcome using image-based authentication. The implementation of image-based authentication can use the Reduced Difference Expansion (RDE) steganography method. application of image-based authentication, utilizing images as authentication media. RDE utilizes the reduced pixel difference as a place to insert credential data. Testing the image in this study, the image has an average similarity of 40 dB, indicating that the image that is inserted with credentials and that is not inserted has a high similarity. The similarity increases the security of the image from theft. The average character capacity that can be accommodated is 21,451 characters, a large enough capacity to accommodate credential data. The image is very sensitive to changes, so there is a slight change in the image, causing the image to not be used for authentication